2010
DOI: 10.1177/0960327109359635
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA strand breaks by comet assay in sputum leucocytes of bitumen-exposed workers: A pilot study

Abstract: DNA strand breaks were determined in leucocytes of induced sputum (IS) and compared with DNA strand breaks in blood lymphocytes from 42 bitumen-exposed workers pre and post shift. Comet assay results were expressed in arbitrary units based on visual scoring (sputum leucocytes) and Olive tail moment (OTM, blood lymphocytes). DNA damage in IS leucocytes was overall high but did not change during shift. Level of DNA strand breaks in IS samples correlated with total cell count and neutrophil content (Spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Three (3.7%) studies were made on welding fumes and solvent based paints [ 96 ], metals (zinc and copper) smelting work [ 60 ], and gold jewellery fumes [ 76 ]. Furthermore, other studies in the selected papers were found, such as polychlorinated dibenzodioxins, metals and silica [ 58 ], perchloroethylene [ 66 ], DDT, DDE together with arsenic and lead [ 73 ], bitumen [ 86 , 87 ], cement [ 98 ], tobacco smoke [ 108 ], and 1-bromopropane [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three (3.7%) studies were made on welding fumes and solvent based paints [ 96 ], metals (zinc and copper) smelting work [ 60 ], and gold jewellery fumes [ 76 ]. Furthermore, other studies in the selected papers were found, such as polychlorinated dibenzodioxins, metals and silica [ 58 ], perchloroethylene [ 66 ], DDT, DDE together with arsenic and lead [ 73 ], bitumen [ 86 , 87 ], cement [ 98 ], tobacco smoke [ 108 ], and 1-bromopropane [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Significantly higher DNA damage levels, as evaluated by the comet assay, were observed in 66 of these studies (81.5%). The remaining studies (n = 15, 18.5%) did not show statically significant results, namely PAH exposure [ 39 , 54 , 55 ], coke-oven PAH exposure [ 106 , 110 , 111 , 114 ], smelting [ 60 ], dust [ 64 , 107 ], traffic air pollution [ 71 ], JP-8 jet fuel [ 79 ], diesel exhaust [ 97 ], bitumen [ 86 ], and tobacco dust [ 108 ]. The study from Cavallo [ 52 ], in six graphene workers and eleven controls, used three comet descriptors, reaching statistically significant results with % DNA in the tail but not by using the tail moment and length.…”
Section: Resultsmentioning
confidence: 99%
“…51 Therefore, p53 is increased upon DNA damage, and combination of the comet assay with detection of molecular markers, such as p53, offers a comprehensive approach for the assessment of DNA damage in vitro. 52 IL-8 expression has been reported to be increased by DNA strand breaks 53 and in renal cancer. 54 CXCL5 is known to be increased in renal cell carcinoma patients, and this change in CXCL5 expression is accompanied by DNA fragmentation.…”
mentioning
confidence: 99%